How the structural deviations on the backbone of conjugated polymers influence their optoelectronic properties and photovoltaic performance - Chochos, Christos L.; Choulis, Stelios A. (My University, 2011)
The design of novel conjugated polymers with appropriate frontier orbital energy levels, low band gap (LBG) and suitable carrier transport properties are needed to improve the power conversion efficiency (PCE) of organic photovoltaic devices. In this review, a detailed structure–property relationship study is presented, by identifying those chemical entities in the backbone of conjugated polymers that are responsible for the modification of optoelectronic properties towards high photovoltaic performance
Keywords: Conjugated polymers; HOMO and LUMO levels; Optical band gap; Organic solar cells; Polymer:fullerene blends